Copyright and citation indices of scientific publications of members of the national academy of sciences of the Kyrgyz Republic (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
As is known, various indicators are used to assess the scientific productivity of scientists and specialists in scientometrics, the most common of which is the Hirsch index or h-index, which is calculated based on citations of works included in a certain database. For the CIS countries, an important publication database is the Russian Science Citation Index (RSCI) database. In the international plan, the Scopus and Web of Sciences databases are widely used. The Hirsch index shows the comparative efficiency of the work of a scientist or a team of scientists. But as is easy to see, according to the indicators of calculating the Hirsch index based on the RSCI databases, for individual scientists, their contribution and participation in collective publications and their citations are not taken into account. Relations between co-authors of collective publications are determined on the basis of an agreement, in the absence of which the copyright for the publication is exercised by all co-authors jointly, and the remuneration is distributed between them equally. It is proposed to introduce a modified Hirsch index, called the Hirsch index “plus” or h+, to assess the individual citation index of scientists’ publications. It is calculated by dividing the usual number of citations of a specific publication by the number of co-authors of the cited publication, which will not cause difficulties in calculating the h+ indices using the algorithm for determining the Hirsch index itself. Such an indicator takes into account the interests of co-authors in terms of copyright, in comparative assessments of their work. Also, to assess the individual citation indices of scientists, it is proposed to introduce the author’s averaging coefficient of indices – kc, equal to the cube root of the total number of co-authors, by which the corresponding Hirsch index or other citation index of a specific author is divided. The article also provides comparative estimates of the Hirsch indices, Hirsch “plus” and these indices taking into account the averaging coefficients of members of the National Academy of Sciences of the Kyrgyz Republic according to the RSCI and Scopus data.
Keywords: scientometrics, copyrights, Hirsch index, modifications of scientometric indices, Hirsch index “plus”, RSCI databases, Scopus and Web of Sciences, co-authors of scientific publications, author’s index averaging coefficient